EFFECTS OF PEDIATRIC PHYSICAL THERAPY ON THE MOTOR DEVELOPMENT OF CHILDREN WITH ASD (REMUNOM, 2025)
Autism Spectrum Disorder (ASD) is a neurodevelopmental condition that significantly affects motor, cognitive, and behavioral skills, impacting the functionality and independence of affected children. This study presents a systematic literature review focusing on the role of pediatric physiotherapy in enhancing motor development in children with ASD, emphasizing specific interventions related to postural control, balance, motor coordination, and gait patterns. Physiotherapy is fundamental for reducing motor deficits, promoting autonomy, and improving quality of life. Scientific evidence supports the effectiveness of physiotherapeutic interventions grounded in evidence-based practices and rigorous methodologies, highlighting the necessity of including physiotherapy as an essential component of multidisciplinary treatment for these children.